Role of Community Colleges for Sustainable Tourism, Innovation & Inclusive Growth : A systematic Review - Gautam, Tara Prasad; Adhikari, Babu Ram; Chand, Hari Bahadur (Community College Research Journal, 2025)
This paper focuses on the changing position of community colleges in Nepal in the move toward sustainable tourism, grassroots innovation, and inclusive economic development. These colleges are established as local institutions that have close connections with the community. They serve to meet the requirements of regional growth, particularly in rural regions where higher education is not regularly provided. Although they enroll over 30 percent of higher education students in Nepal, their development contributions have not received much attention in the literature, and research in the development field has primarily focused on academic access and institutional constraints. This paper bridges that gap by applying a systematic literature review and an analysis of specific cases to the Nepali context. We employed thematic analysis to group 40 high-quality scholarly and policy resources in order to examine the contributions, challenges, and possibilities through which community colleges can play a role. The results show that community colleges promote sustainable tourism through eco-tourism, cultural preservation, and hospitality training programs; promote entrepreneurship through vocational training and incubators; and enhance social inclusion through affordable education for women and other frequently marginalized groups. There are instances of community colleges that demonstrate effective outcomes through curriculum and community-led projects. The paper ends with specific policy suggestions to enable community colleges to serve as strategic platforms for achieving Nepal’s targets of Green, Resilient, and Inclusive Development (GRID) and the Sustainable Development Goals (SDGs). Governance, curriculum, and partnerships should be reformed in order to maximize their potential to transform the development landscape in Nepal.